1989
DOI: 10.1021/la00088a025
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of trimethylphosphine in zeolite Y: a solid-state NMR study

Abstract: The oxidation of trimethylphosphine (TMP) to trimethylphosphine oxide (TMPO) has been followed in Y-type zeolites by using 31P MAS-NMR spectroscopy. In a Na-Y zeolite, TMP coordinates weakly with Na+ ions to give a resonance at -59.5 ppm. This form of TMP is readily oxidized at 25 °C to TMPO, which may be coordinated to Na+ (48.6 ppm) or may be physisorbed (41.4 ppm). Similarly, TMP which is weakly bound to a Lewis acid site (-61.5 ppm) in a dealuminated zeolite may be easily oxidized to Lewis-bound TMPO (56 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 1 publication
2
37
0
Order By: Relevance
“…The observation of a peak at +65.7 ppm on ZrO 2 −S is intriguing. This signal is clearly separated from spinning sidebands of HTMP + species at the MAS frequency of 8 kHz (see spectrum b of Figure ) and can be attributed to a protonated OTMP species . In contrast to Coster et al., Lunsford et al also observed a peak at approximately this position, which was, however, superimposed by spinning sidebands.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The observation of a peak at +65.7 ppm on ZrO 2 −S is intriguing. This signal is clearly separated from spinning sidebands of HTMP + species at the MAS frequency of 8 kHz (see spectrum b of Figure ) and can be attributed to a protonated OTMP species . In contrast to Coster et al., Lunsford et al also observed a peak at approximately this position, which was, however, superimposed by spinning sidebands.…”
Section: Discussionmentioning
confidence: 73%
“…Zalewski et al were able to show that HOTMP + only formed on very strong Brønsted acid centers in HY zeolites. Lunsford et al, in their study of TMP adsorption on sulfated ZrO 2 , argued that the oxidation of TMP to OTMP occurred by traces of O 2 being present during the sample preparation and handling for NMR measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant drawback of trialkylphosphines as probe molecules is their ability to oxidize during adsorption over zeolites. 17 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…PMe3 is a sterically large, soft (class B) Lewis base, compared to H20, a small, hard (class A) Lewis base molecule[128]. Binding of PMe3 to Brcnsted and Lewis acid sites in zeolite Y has been probed in several studies using 31P MAS[69,144,145,146].Figure 6.7 features the 23Na DOR spectra of Na56Y zeolite, loaded with quantitative amounts of PMea guest molecules. The adsorbed PMe3 molecules clearly affect the environments of the sodium nuclei, causing profound changesin the positions and shapes of the _3Na signals, as shown in Figure 6.7.…”
mentioning
confidence: 99%